The Renal and Liver Complications Development among Patients with Type 2 Diabetes Mellitus in Kirkuk City - Wasan Talib Abed; Walaa Esmael Jassim; Emad Mohamed Rasheed (Journal of Techniques)
Diabetes is a chronic metabolic malady that has raised levels of blood glucose, which in last, it will cause severe harms to the heart, blood vessels, eyes, kidneys, and nerves. In this article trials to investigate the development of the renal and liver disorders among patients with T2DM in a population of Kirkuk city. The hospital-based cases- control study was conducted for patients with T2DM patients that attended the diabetic clinics in Kirkuk during the period from March 2021– to August 2021 and were screened for serum conc. of liver function tests (Alanine Aminotransferase (ALT), Aspartate Aminotransferase (AST) and Alkaline Phosphatase (ALP)), renal function tests (Creatinine and Urea) especially with (family history of diabetes, & hypertension.  Patients recruited for this study, showed serum urea and creatinine significantly more than that in control, p < .001, while for renal glomerular filtration rates significantly lower than that in control group, p < 001. Their kidney disease stage frequencies were significantly different in diabetic patients than in control P< 0.001. Stage (II) was the most frequently stage within the T2DM group (n = 58, 58%), while stage (I) was the most frequently observed category within the control group (n = 28, 56%). The mean of AST for T2DM (30.63± 6.08) was significantly more than that in the control (25.13± 4.32). T2DM reveal significant differences in the mean value (32.51± 8.96) of ALT which was more than the control (20.59± 4.38). The estimation of GFR as soon as possible with testing of urea and creatinine confirms the diagnosis of renal disease and staging of the renal disease. The liver enzymes illustrate in T2DM a significant correlation in comparison to the control group.